KREATIVITAS GURU DALAM PEMBELAJARAN IPA DI SEKOLAH DASAR - Mujakir Mujakir (UIN AR-RANIRY, 2015)
This research aims to reveal the creativity of the Inpres elementary school teachers in learning science and to build a specific theory based on the components of teachers’ creativity in selecting and using the media in learning science, factors that support teachers' creativity in developing materials, developing methods, and the steps conducted by the school in developing the teachers’ creativity. This research uses a qualitative phenomenologic interpretive by applying naturalistic model of Guba. The determination of research information was done purposively. Subjects of the research were teachers who taught science at grades IV, V, and VI. Data were collected through observation, interviews and documentation analysis, and were analyzed using the Bogdan model analysis. The data validation was obtained through perseverance of observation and triangulation. The triangulation was done with respect of sources, methods, and theory. Results of this research is in the form of a specific theory that the principal’s idea to improve the academic quality could encourage the teachers’ creativity in the science teaching and learning process at the public elementary school “Inpres Sido